Intangible resources: the relevance of training for European firms' innovative performance - Daria Ciriaci (European Commission, Joint Research Centre (JRC), 2011)
This paper assesses whether European firms' innovative performance is impacted by investments in training directly aimed at developing and/or introducing innovation, in addition to the scale of a firm's investments in innovation proxied by the number of R&D personnels. In particular, it explores the complementarity between these two factors (in the presence of a well-trained workforce, the knowledge created by a firm's R&D personnel can be better exploited), and their dependence on a firm's knowledge intensity (high versus low % of tertiary-educated workforce) and size (SMEs versus large firms). Using European CIS non-anonymised data for the period 1998-2000, this paper estimates a system of simultaneous equations in which investments in training and stock of R&D personnel are treated as endogenous in relation to the innovative sales on which they are presumed to have an effect. The choice to use this time period rather than more recent ones – to which I had access at the Eurostat Safe Centre – is data-driven. It has better information on training expenditures and it is the last period to provide firm-level information on the number of employees with tertiary education. Unlike the majority of CIS-based studies, the main variables of interest are continuous ones, while dummy variables are used as controls only. Empirical evidence confirms most previous results – investment in training and stock of R&D personnel positively affects firms' innovativeness – but also provides some important additional insights. Ceteris paribus, returns to training and R&D personnel are not affected by the knowledge intensity of the firm, while are always statistically significantly higher in large than in small and medium sized firms. However, while in the case of training the differences in returns between SME and large firms are small, in the case of R&D personnel are quite pronounced.
Keywords: O30; O31; O32; D83; D62; 330; Intangibles; R&D investment; human capital; CIS; CDM model